Wage and employment cyclicalities at the establishment level - Christian Merkl; Heiko Stüber (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2023)
Although the quantitative relationship between employment cyclicality and wage cyclicality is central for the dynamics of macroeconomic models, there is little empirical evidence on this topic. We use the German AWFP dataset to document that wage cyclicalities are very heterogeneous across establishments. Based on this heterogeneity, we estimate the relationship between employment cyclicality and wage cyclicality at the establishment level. We use this micro-estimate as a calibration target for a macro labor market flow model with heterogeneous wage dynamics that nests the standard search and matching model. Based on this micro-macro linkage, we provide a new quantitative benchmark for the role of wage rigidity in search and matching models. Furthermore, we show that acyclical and countercyclical wage establishments are key drivers for stronger labor market reactions in recessions than in booms.
Keywords: E32; E24; J64; 330; Wage Cyclicality; Employment Cyclicality; Labor Market Flow Model; Labor Market Dynamics; Establishments; Administrative Data